Perancangan Dashboard untuk Visualisasi Harga dan Pasokan Beras di Pasar Induk Beras Cipinang - Dedi Sugiarto; Is Mardianto; Muhammad Najih; Daniel Adrian; Dimas Adi Pratama (Jurnal Teknologi Industri Pertanian, 2021)
Food Station is a city-owned enterprise owned by the Jakarta Provincial Government whose tasks include monitoring and publication of supply data and rice price through Cipinang Rice Market so that it is useful as a guide for traders and policy makers in relevant government institutions. This study aims to design a dashboard to visualize the price and supply of rice through Cipinang Rice Market. The research stages consist of identification of information requirement, data warehouse design and On-line Analytical Processing (OLAP) database, transfer of operational data from excel file and web scrapping into OLAP database through Extract, Transform, Load (ETL) process and create dashboard using PowerBI application. The result of this research is a data warehouse that can facilitate the analysis with some fact table that is price, quantity of rice enter, quantity of rice out and stock and some dimension table that is place dimension (city of origin / destination), dimension time, dimension of rice type and dimension market and dashboard of various price and supply charts that can be selected based on available dimensions. Keywords: dashboard, data warehouse, rice price, rice supply, visualization